1988
DOI: 10.2136/sssaj1988.03615995005200050035x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency and Nitrogen Budget for Conservation Tilled Wheat

Abstract: The understanding of nitrogen (N) cycling in the soil‐plant‐atmosphere is necessary to maximize N use efficiency and to develop N budgets for wheat (Triticum aestivum L.) production. The objectives of this study were to determine the relative uptake rates of residual soil N and fertilizer N in conservation tilled winter wheat. These data were combined with soil mineralization and aerial NH3 flux data to present a N budget for the soil‐plant‐atmosphere system. Fertilizer N uptake was determined using ammonium n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Differences in the depth of the roots system have an affect on the plants ability to retain N from different soil layers (Burns, 1980) and are, therefore, important for NUE. Moreover, the placement of fertilizer N below the surface soil layer can decrease immobilization and increase plant uptake of N (Sharpe et al, 1988) for the shallow-rooted species as grasses (Thorup-Kristensen and Nielsen, 1998). The reduction in the NUE due to fertilization was not unexpected, as similar results having been found by other researchers (Gauer et al, 1992;Delogu et al, 1998) who reported that NUE decreases with increasing nitrogen availability.…”
Section: Discussionsupporting
confidence: 73%
“…Differences in the depth of the roots system have an affect on the plants ability to retain N from different soil layers (Burns, 1980) and are, therefore, important for NUE. Moreover, the placement of fertilizer N below the surface soil layer can decrease immobilization and increase plant uptake of N (Sharpe et al, 1988) for the shallow-rooted species as grasses (Thorup-Kristensen and Nielsen, 1998). The reduction in the NUE due to fertilization was not unexpected, as similar results having been found by other researchers (Gauer et al, 1992;Delogu et al, 1998) who reported that NUE decreases with increasing nitrogen availability.…”
Section: Discussionsupporting
confidence: 73%
“…The rye vs. wheat data in Tables 2 and 3 also contain a noteworthy inconsistency, with the lysimeter data (Table 2, Year 1) indicating less NO 3 –N leaching for rye compared with wheat but with the cover crop data (Table 3, Years 1 and 3) indicating numerically lower aboveground total N for rye compared with wheat. Our data are incomplete for resolving this inconsistency, but we propose two hypotheses for further thought: (i) greater belowground dry matter is produced in rye compared with a modern wheat variety selected for high yield and short straw, which is supported by larger root dry matters in old vs. modern wheat varieties measured by Siddique et al (1990), and/or (ii) there are greater gaseous N losses from rye due to soil denitrification, aboveground N losses during anthesis (Rumburg and Sneva, 1970), or ammonia volatilization during maturation (Schjoerring and Mattsson, 2001; Sharpe et al, 1988). Further cover crop research is needed to understand the processes producing N conservation in winter cereals.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States alone, N additions to cropping lands have increased from 9.6 million to 10.9 million tons between 197810.9 million tons between and 200810.9 million tons between (IFA 2008. The demand for higher yielding crops and, more recently, biofuel production will likely continue to increase the demand for and use of fertilizer N. Plant recovery of applied N fertilizers must be efficient to reduce crop production costs and N losses to both the atmosphere and groundwater (Sharpe et al 1988).…”
Section: Introductionmentioning
confidence: 99%